Análise proteômica diferencial da interação incompatível entre o feijão-de-corda e o fitopatógeno Colletotrichum gloeosporioides (Penz.) Penz. & Sacc - Moura, Hudson Fernando Nunes (2013)
Cowpea [Vigna unguiculata (L.) Walp.] belongs to the family Fabaceae and is widely used in food as a source of protein, carbohydrates, vitamins and minerals. Among the main features of cowpea, its high protein content and good tolerance to conditions of low water availability in soils, high temperatures and relative tolerance to salinity conditions typical of semi-arid regions of northeastern Brazil, are some of which can be cited. However, despite the considerable capacity of tolerance to different stress conditions, the productivity of cowpea is threatened by the action of various pathogens, among which stand out as major causes of fungal diseases of this crop, the example of Anthracnose as a result of infection by C. gloeosporioides, characterized by reddish-brown spots on the leaf veins that can be extended by all organs of the host plant. Fortunately, the cowpea has cultivars that have different characteristics of resistance against C. gloeosporioides, regarding the activation of plant defenses in incompatible interactions said, given that the pathogen is unable to resolve the infection. From this premise, it is worth mentioning that most of the mechanisms of plant resistance to pathogens is related to the differential gene expression of proteins that act as markers of defense in response to infection. Thus, this study proposes a differential proteomic analysis of the incompatible interaction (resistance) between plants of cowpea genotype BR3, and isolated LPVD-1, the fungus C. gloeosporioides in order to identify potential protein markers for the determinants of this resistance pathossystem. By using the approach 2D-PAGE in addition with mass spectrometry ESI-Q-TOF MS / MS, we have identified 118 differentially expressed proteins, whereas proteins overexpressed (102) and down-expressed (16), involved in various cellular processes, such as : energy metabolism, photosynthesis, protein and nucleic acids metabolism, stress response, cellular transport, redox homeostasis, signaling and defense, with emphasis on expression of PR-10 proteins (pathogenesis-related), remorina and ascorbate peroxidase that had significant alterations at all time points tested. These findings demonstrate the complexity of the mechanisms involved in plant resistance and assist in directing the programs of genetic improvement of this crop against fungal attack. Furthermore, it’s promoting the understanding of the biochemical and physiological interconnections arising from incompatible plant-fungus interaction.